Cytochrome C oxydase 1 gene sequences long-barbel sheatfish, Kryptopterus limpok (Bleeker, 1852) from Kampar River and Indragiri River of Riau Province - Roza Elvyra; Dedy Duryadi Solihin (Jurnal Iktiologi Indonesia, 2015)
This study aimed to analyze the sequence of mitochondrial DNA cytochrome c oxydase 1 (Cox-1) gene of the long barbel sheatfish, Kryptopterus limpok. The Cox-1 gene of Kryptopterus limpok from Kampar and Indragiri Rivers, Riau Province was amplified using PCR technique. The length of the Cox-1 gene sequence was 655 bp containing nine nucleotide sites substituted. Four base substitutions were transition and five base was transversion. Nucleotide frequencies of guanine was a few (G:17.2%) and approximately equal in frequencies of cytosine, thymine, adenine (C: 29.5%, T: 27.5%, A: 25.8%), and G+C content (46.7%). The genetic distance of mtDNA Cox-1 gene sequences between Kryptopterus limpok from Kampar and Indragiri river was 0.01. Phylogenetic tree showed that Kryptopterus limpok from Kampar and Indragiri Rivers are in one cluster with 100% bootstrap value. Abstrak Penelitian ini bertujuan untuk menganalisis runutan gen cytochrome c oxydase 1 (Cox-1) DNA mitokondria ikan lais janggut, Kryptopterus limpok. Gen Cox-1 Kryptopterus limpok dari Sungai Kampar dan Indragiri, Provinsi Riau telah diamplifikasi menggunakan teknik PCR. Runutan gen Cox-1 yang diperoleh sepanjang 655 bp, dengan sembilan situs substitusi nukleotida, meliputi empat substitusi transisi dan lima substitusi transversi basa. Frekuensi nukleotida yang sedikit ditemukan pada guanin (G:17,2%), sedangkan frekuensi cytosin, thymin, adenin kurang lebih sepadan (C: 29,5%, T: 27,5%, A: 25,8%), dan kandungan G+C (46,7%). Jarak genetik runutan gen Cox-1 antara Kryptopterus limpok dari Sungai Kampar dan Sungai Indragiri adalah 0,01. Pohon filogeni memperlihatkan bahwa Kryptopterus limpok dari Sungai Kampar dengan Sungai Indragiri membentuk satu kelompok dengan nilai bootstrap 100%.